PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE TEAM QUIZ TERHADAP HASIL BELAJAR BIOLOGI DITINJAU DARI KEAKTIFAN BERTANYA PADA SISWA SMA NEGERI 1 KARANGPANDAN TAHUN PELAJARAN 2011/2012 - Wulantika, Alyuni; Harlita, Harlita; Ariyanto, Joko (Pendidikan Biologi, 2011)
ABSTRACT ? The purposes of this research were to know: 1) the influence of team quiz  active learning strategy to the result of study biology; 2) the influence of student?s learning asks activity to the result of study biology; 3) the interaction between learning strategy and aska activity to the result of study biology. This research was  quasi experiment research using  Randomized Control Only design. Learning strategy and asks activity were independent variables and student?s achievement of study biology was the dependent variable. The population of this research was all of  XI grade of natural science students of SMA Negeri 1Karangpandan. The samples of this research were the students of class XI IPA 4 as the control group and students of class XI IPA 3 as the experimental group.  The sample of this research was established by cluster random sampling. The data about the result of study biology collected by use test and observation. Asks activity meansured by using questionnaires. The analisis of this research was anava two away in different cell and the advance test used Bunfferoni test. The conclusion of this research were: 1) Team Quiz active learning strategy had significant influence to the result of study biology in pshycomotor domain but didn?t have significant influence in cognitive domain and affective on XI grade of SMA Negeri 1 Karangpandan; 2) Asks activity had significant influence to the result of study biology on XI grade of SMA Negeri 1 Karangpandan; 3) There wasn?t interaction between  learning strategy and asks activity  to  the result of study biology on XI grade of SMA Negeri 1 Karangpandan. Keywords: student?s biology achievement, active learning strategy, team quiz, and ask  activity